2023
DOI: 10.3390/antiox12030772
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Guanidine Acetic Acid Improves Ruminal Antioxidant Capacity and Alters Rumen Fermentation and Microflora in Rapid-Growing Lambs

Abstract: Guanidine acetic acid (GAA) has been reported to improve growth performance, nutrient utilization, and meat quality in livestock. This study aimed to investigate whether coated GAA (CGAA) in comparison with uncoated GAA (UGAA) could have different effects on rumen fermentation, antioxidant capacity, and microflora composition in the rumen. Seventy-two lambs were randomly arranged in a 2 × 3 factorial experiment design with two diets of different forage type (OH: oaten hay; OHWS: oaten hay plus wheat silage) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…In our study, the addition of GAA increased CAT levels and decreased MDA levels in the blood of Angus steers, suggesting that GAA enhanced the antioxidant capacity of steers. This is consistent with previous studies [18]. Creatine has been reported to have the ability to remove O2- [44], and the changes in creatine concentration in this study coincided with the changes in antioxidant indices.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the addition of GAA increased CAT levels and decreased MDA levels in the blood of Angus steers, suggesting that GAA enhanced the antioxidant capacity of steers. This is consistent with previous studies [18]. Creatine has been reported to have the ability to remove O2- [44], and the changes in creatine concentration in this study coincided with the changes in antioxidant indices.…”
Section: Discussionsupporting
confidence: 93%
“…This process involves not only energy metabolism but also N deposition (nitrogen metabolism) in the beef cattle organism [17]. In addition, GAA has been reported to enhance the antioxidant capacity of the rumen in ruminants [18]. In summary, GAA has the potential to improve growth performance in ruminants, but little is known about the effects of GAA on production performance and nitrogen metabolism in Angus steers; furthermore, it remains to be explored whether the addition of high doses of GAA would have a linear superimposed effect on the metrics in Angus steers.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in TVFA production was in line with the bacteria populations [31], indicating that GAA addition has a positive influence on nutrient degradation and microbial growth [41]. However, the introduction of excessive GAA may have inhibited TVFA production, this may be related to the effect of GAA overdose on rumen homeostasis [42], and it suggests that GAA coating is necessary for ruminants. However, we did not observe a change in the proportion of individual volatile acids, and this finding is inconsistent with the research on cows, which has demonstrated that GAA can alter the fermentation pattern and promote the formation of propionic acid [31]; this may be related to a lower NDF of the basal diet [43].…”
Section: Final Ph Nh 3 -N Mcp and Vfa Patternmentioning
confidence: 82%
“…However, it has been reported that the addition of GAA in the diet can decrease the asymptotic production and the production rate of GP [44], which was observed in the AH100 diet when increasing the dose of GAA, which is attributed to the proportion of short-chain fatty acids (SCFA), since GAA favors the formation of propionate [45], an SCFA that produces less gas compared to acetate and butyrate [46]. In addition, the lag phase also increased in this diet; although it did not show a trend with an increasing dose of GAA, this increase can be attributed to the time that ruminal microorganisms require to adapt to the presence of GAA, since it is susceptible to degradability when it is not rumen protected [47], and microorganisms can use it as a source of energy and nitrogen to synthesize their proteins [45]. However, with an increase in GAA, GP production increased in the AH10 diet, while in the AH100 diet, GP production decreased with increased GAA dose.…”
Section: In Vitro Ruminal Total Gas Productionmentioning
confidence: 88%